PENINGKATAN KREATIVITAS MOTORIK HALUS PADA ANAK USIA DINI MELALUI KEGIATAN MENGGAMBAR DI TAMAN KANAK-KANAK WIDYA KUMARA DESA WERDI BHUWANA KECAMATAN MENGWI KABUPATEN BADUNG - Diah Yuniari I Gusti Ayu (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
This study investigates the process of improving fine motor creativity of children aged 5-6 years through drawing activities. Drawing activities are selected based on the suitability of the needs and characteristics of children aged 5-6 years, at which age the children are still in the play and imitation phase. This research is very relevant to the field of early childhood education, this is based on this research examining the suitability of programs with needs. Therefore, this research is very important to do to determine the results of the application of drawing strategies in improving children’s creativity. This study focuses on strategies to improve children’s fine motor creativity. The process of extracting data was carried out using observation, interview, and literature study techniques. These three techniques lead researchers to come into direct contact with phenomena in the field. The data that has been collected and reduced are analyzed using constructivism theory. The data that has been analyzed is then presented in a qualitative descriptive form. Based on the results of the analysis carried out, it was found that in the strategy the teacher had taken actions that led to the habituation of the child so that the child would get used to the activity. The habit of children in participating in drawing activities will arouse children’s self-confidence to find their ways and patterns in completing their drawing tasks, from the research results it was found that not all students develop according to expectations (BSH). The habituation process is carried out by (1) inviting students to learn outside the classroom, (2) providing the material that is easy for students to understand, and (3) implementing supervision, assistance, and mentoring measures. Learning outcomes are then measured using portfolio techniques. Portfolio assessment techniques are believed to be able to measure the success rate ofchildren every day.